Extracellular Superoxide Dismutase Is Associated With Left Ventricular Geometry and Heart Failure in Patients With Cardiovascular Disease. Issue 15 (4th August 2020) - Li, Xiuwen; Lin, Yingying; Wang, Shaohua; Zhou, Shiyi; Ju, Jingmeng; Wang, Xiaohui; Chen, Yangxin; Xia, Min
Abstract : Background: Extracellular superoxide dismutase (Ec‐SOD) is a major scavenger of reactive oxygen species. However, its relationships with abnormal left ventricular (LV) geometry patterns and heart failure (HF) are still unknown in patients with cardiovascular disease. Methods and Results: A cross‐sectional study was carried out to evaluate the association of serum Ec‐SOD activity with LV geometry, as well as HF in 1047 patients with cardiovascular disease. All participants underwent standard echocardiography examination and measurement of serum Ec‐SOD activity. Overall, we found a significantly decreased trend of serum Ec‐SOD activity from subjects with normal geometry (147.96±15.94 U/mL), subjects with abnormal LV geometry without HF (140.19±20.12 U/mL), and subjects with abnormal LV geometry and overt HF (129.32±17.92 U/mL) after adjustment for potential confounders ( P for trend <0.001). The downward trends remained significant in the concentric hypertrophy and eccentric hypertrophy groups after stratification by different LV geometry patterns. Multinomial logistic regression analysis showed that each 10 U/mL increase in serum Ec‐SOD activity was associated with a 16.5% decrease in the odds of concentric remodeling without HF (odds ratio [OR], 0.835; 95% CI, 0.736–0.948), a 40.4% decrease in the odds of concentric hypertrophy with HF (OR, 0.596; 95% CI, 0.486–0.730), a 16.1% decrease in the odds of eccentric hypertrophy without HF (OR, 0.839; 95% CI, 0.729–0.965) and a 34.0% decrease in the odds of eccentric hypertrophy with HF (OR, 0.660; 95% CI, 0.565–0.772). Conclusions: Serum Ec‐SOD activity was independently associated with abnormal LV geometry patterns with and without overt HF. Our results indicate that Ec‐SOD might be a potential link between LV structure remodeling and the development of subsequent HF in patients with cardiovascular disease. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier NCT03351907.